2021
DOI: 10.1186/s12889-021-10852-3
|View full text |Cite
|
Sign up to set email alerts
|

Global effect of COVID-19 pandemic on physical activity, sedentary behaviour and sleep among 3- to 5-year-old children: a longitudinal study of 14 countries

Abstract: Background The restrictions associated with the 2020 COVID-19 pandemic has resulted in changes to young children’s daily routines and habits. The impact on their participation in movement behaviours (physical activity, sedentary screen time and sleep) is unknown. This international longitudinal study compared young children’s movement behaviours before and during the COVID-19 pandemic. Methods Parents of children aged 3–5 years, from 14 countries (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
145
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(168 citation statements)
references
References 31 publications
10
145
2
1
Order By: Relevance
“…Preliminary and largely self-reported evidence from around the world indicates that during the pandemic, children were more sedentary, engaged in more screen time 35 and less physical activity, 9 , 36 , 37 ate more unhealthy and fewer healthy foods, 9 , 38 and experienced later and more variable sleep schedules. 39 , 40 Engagement in similar behaviors is likely the behavioral mechanism responsible for the accelerated BMI gain in this study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Preliminary and largely self-reported evidence from around the world indicates that during the pandemic, children were more sedentary, engaged in more screen time 35 and less physical activity, 9 , 36 , 37 ate more unhealthy and fewer healthy foods, 9 , 38 and experienced later and more variable sleep schedules. 39 , 40 Engagement in similar behaviors is likely the behavioral mechanism responsible for the accelerated BMI gain in this study.…”
Section: Discussionmentioning
confidence: 65%
“…29 Furthermore, preliminary, largely self-report studies indicate that children's health behaviors have deteriorated during the COVID-19 pandemic. 9 , 35 , 36 , 37 , 38 , 39 , 40 , 41 Thus, the objective of this study is to evaluate the impact of the COVID-19 pandemic on children's zBMI.…”
Section: Introductionmentioning
confidence: 99%
“…Other papers have focused on sleep schedules/sleep quality in children as well as the suggested WHO recommendations [ 1 , 15 , 16 ]. They aimed to provide strategies for permanent behavior change in order to ensure the health and well-being of children during the COVID-19 pandemic, as well as indications of conditions enabling preschoolers to practice healthy movement behaviours and to meet the global guidelines [ 8 , 17 , 18 , 19 , 20 ]. Young children are directly influenced by their environmental patterns and family behavior.…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, living in rural areas was also reported as a factor positively related to smaller decreases in physical activity, declines in sleep quality and increases in screen time ( 25 ). In this context, a study conducted in 14 countries showed that preschoolers who were able to go outside during the pandemic were more likely to meet the PA guidelines ( 26 ). To compensate for the lack of opportunity for some children who live in urban areas, strategies should provide opportunities to access green spaces or open spaces to play in cities while considering physical distancing due to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Young children's movement behaviors (physical activity, sedentary behavior and sleep) have been negatively impacted during the pandemic ( 25 , 26 ). This in turn has the potential of affecting other areas of health and development ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%